Pengaruh Integritas Mahasiswa, Minat Belajar, Dan Penyalahgunaan Teknologi Informasi Terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi Sebagai Calon Akuntan - Fuadah, Luluk Atin; Zanaria, Yulita; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to analyze Student Integrity, Interest in Learning and Misuse of Information Technology on Academic Fraudulent Behavior of Accounting Students as Prospective Accountants. The type of research used in this study was quantitative, in this study the researchers used primary data through questionnaires and a population of 195 students. The sampling technique used the slovin formula so that 95 respondents were obtained. Data analysis in this study used hypothesis testing. The results of this study indicate that student integrity affects the academic fraud behavior of accounting students as prospective accountants, learning interest does not affect the academic fraud behavior of accounting students as prospective accountants, misuse of information technology affects the academic fraud behavior of accounting students as prospective accountants, student integrity, interest. Learning and Misuse of Information Technology jointly affect Academic Fraud of Accounting Students as prospective accountants.